CDKN2AIP-induced cell senescence and apoptosis of testicular seminoma are associated with CARM1 and eIF4β - Cao Yuming; Chen Zhenlie; Qin Zihan; Qian Kaiyu; Liu Tongzu; Zhang Yuanzhen (Acta Biochimica et Biophysica Sinica)
Testicular seminoma is a relatively rare tumor which is mostly detected in male population aged from 15 to 35 years old. Although several molecular biomarkers have been identified to be associated with testicular seminoma pathogenesis, the exact mechanism for testicular seminoma progression remains largely unknown. CDKN2A interacting protein (CDKN2AIP) has previously been identified as a tumor suppressor in multiple malignant diseases. In this study, we aimed to further explore its role in testicular seminoma as well as the underlying molecular mechanisms. Retrospective testicular seminoma clinical samples, normal tissues, NTERA-2 cell line, and mouse xenograft models were used in this study. RT-qPCR, western blot analysis, immunofluorescence microscopy, Co-IP and IP-MS experiments were performed to detect the expression of CDKN2AIP and its interaction with CARM1 and eIF4β. SA-β-gal staining assay and H3K9me3 activity experiments were used to subsequently evaluate the cell senescence and apoptosis. Mouse xenograft animal model was used for in vivo study. The results showed that CDKN2AIP is highly expressed in normal testis samples, and is significantly suppressed in testicular seminoma clinical samples and cell line model. Up-regulation of CDKN2AIP is significantly associated with the inhibition of testicular seminoma tumor growth and the increase of cell senescence and apoptosis. CDKN2AIP exhibits anti-tumor activity by interacting with CARM1 and eIF4β. CDKN2AIP induces testicular seminoma cell senescence by suppressing CARM1 expression and eIF4β phosphorylation. The CDKN2AIP-CARM1 and CDKN2AIP-eIF4β interactions, which induce tumor cell senescence and apoptosis, may be the potential druggable molecular pathways in testicular seminoma tumor pathogenesis and progression.